Primary splenic hydatidosis - Manandhar, Kishor (Journal of Patan Academy of Health Sciences, 2018)
Hydatid disease is becoming a public health problem in Nepal. Majority of the patients have hydatidosis of liver and lungs. Primary splenic hydatidosis is rare. The clinical presentation of primary splenic hydatidosis is similar to other cystic splenic pathologies. It presents with slow growing, dull aching left upper quadrant abdominal lump. Ultrasonography and computed tomography scans are helpful in diagnosis. We report a 36 years lady with primary splenic hydatidosis, who successfully underwent open en bloc resection of hydatid cyst along with total splenectomy.